The Role of Chinese Trade in the Economic Stability of Kyrgyzstan and Tajikistan - Iman Bastanifar; Kashif Hasan Khan; Abdulmelik Alkan (Contemporary Chinese Political Economy and Strategic Relations: An International Journal)
This study explores the feasibility of forging trade partnerships between Kyrgyzstan and Tajikistan, emphasizing the crucial role of economic stability in determining trade effectiveness considering the significance of the Belt and Road Initiative (BRI) in the region. Using the Morris technique, for measuring economic stability index, the research examines key variables such as inflation rates, unemployment rates, private debt metrics, loans and debt securities relative to gross domestic product (GDP), and government gross debt as a percentage of GDP. Granger Causality analysis has been applied for understanding the relationship between trade partnerships and economic stability index. Spanning from 2000 to 2021, this comprehensive analysis offers valuable insights into economic trends in both nations. The findings reveal similar levels of economic stability on average, with Tajikistan showing slightly higher stability since 2013 due to demographic factors and shifts in trade ratios to GDP. Kyrgyzstan averages a stability score of 63 percent, marginally lower than Tajikistan’s 65 percent. The trade partnerships enhance the economic stability of Kyrgyzstan, while there is no significant relationship for the economy of Tajikistan. Therefore, Kyrgyzstan should be keen on following BRI projects for its economic stability.